PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2008-2011 - Putri Tirtasari; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
Based on the empirical fact that intellectual capital (IC) still undergoes and the other fact that there is inconsistency between the former researches about the influence of IC to company’s performance, this study is done. This study aims to investigate the influence of IC to company’s current perfomance and company’s future performance, the influence of Rate of Growth of Intellectual Capital (ROGIC) to company’s future performance, and last but not least is to investigate the influence of IC to company’s  future performance differs by its industry.This study uses two independent variabels which are IC and ROGIC that are measured with Model Pulic (Value Added Intellectual Coefficient a.k.a VAICTM). Whereas the dependent variabel on this study is company’s performance that measured with ROE, EPS, ASR. The population on this study consists of all listed companies in Indonesia Stock Exchange in the year 2008-2011, except banking sectors. Then, the sampels of this study are 64 companies that are chosen with purpossive sampling criterions. The data used are 256 company’s annual financial reports. The data is analysed using PLS-regression.The results of this study show that IC is positively and significantly related to company’s performance, IC is positively and significantly related to company’s future performance, ROGIC negatively and not significantly related to company’s future performance, and the influence of IC to company’s  future performance differs by its industry.